Estudio de factibilidad para la creación de una empresa comercializadora de CupCakes (2016)
This feasibility study for the creation of enterprise, aims to leverage the tools and conditions that the national government gives the country's agribusiness sector in order to encourage the creation and growth of SMEs (Small and Medium Enterprises ) . Focusing them to exploitation of national resources. Then became a possible analysis of potential markets and the advantages offered by each of them, achieving the identification of the target market were evaluated. In this study, the study included all rules, regulations and supplementary information that ultimately helped create entry strategies and plan how to properly advisable to enter the market operation of the city of Santiago de Cali - Valle del Cauca.